2017
DOI: 10.4269/ajtmh.17-0436
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Mutations Associated with Antifolate and Chloroquine Resistance among Imported Plasmodium vivax in the State of Qatar

Abstract: is the most prevalent parasite worldwide, escalating by spread of drug resistance. Currently, in Qatar, chloroquine (CQ) plus primaquine are recommended for the treatment of malaria. The present study examined the prevalence of mutations in dihydrofolate reductase (), dihydropteroate synthase () genes and CQ resistance transporter () genes, associated with sulphadoxine-pyrimethamine (SP) and chloroquine resistance, among imported cases in Qatar. Blood samples were collected from patients positive for and seeki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
1
9
1
1
Order By: Relevance
“…Similar frequency of insertion was reported by in vitro susceptibility to CQ studies using isolates from Thailand (46%) and Myanmar (56%) [ 13 ]. More recent studies have also demonstrated K10 insertion in isolates of P. vivax from India [ 32 , 33 ] and Ethiopia [ 44 ], but the frequency was lower than that found in our study. Among the samples from India, a high frequency of polymorphisms in the pvcrt - o and pvmdr1 genes has been demonstrated also, indicating the circulation of strains that may acquire CQRPv phenotype in that region [ 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Similar frequency of insertion was reported by in vitro susceptibility to CQ studies using isolates from Thailand (46%) and Myanmar (56%) [ 13 ]. More recent studies have also demonstrated K10 insertion in isolates of P. vivax from India [ 32 , 33 ] and Ethiopia [ 44 ], but the frequency was lower than that found in our study. Among the samples from India, a high frequency of polymorphisms in the pvcrt - o and pvmdr1 genes has been demonstrated also, indicating the circulation of strains that may acquire CQRPv phenotype in that region [ 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 91%
“…Chloroquine and PQ are still the drugs of choice for the treatment of P. vivax in some countries, especially in Latin America [ 28 31 ]. However, CQRPv has emerged in several parts of the world [ 32 , 33 ], including Malaysia [ 30 ], Myanmar [ 34 ], India [ 33 ] and Brazil [ 7 , 35 ]. The molecular mechanism of CQRPv is still not well defined.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) estimates that 3.3 billion people are at risk of malaria infection, 219 million clinical cases and 435,000 deaths globally in 2017 [1]. Qatar has been free from local malaria transmission since 1970 [2], however, an influx of migrant workers from malaria-endemic countries, representing a major threat for re-introduction of local drug resistance malaria transmission [3][4][5][6]. In addition to the flow of imported cases, the receptivity and risk of malaria reintroduction are evident by the presence of the mosquito vectors, Anopheles stephensi and An.…”
Section: Introductionmentioning
confidence: 99%
“…Émigrés constitute the majority of residents in GCC countries, reaching > 80% in Qatar [8]. In the last two decades there has been an increase in the flow of migrant workers to Qatar, associated with a positive trend in reported cases of imported malaria [7,9,10]. In addition to the increase in imported cases, the receptivity and risk of malaria reintroduction is evident by the presence of the mosquito vectors, Anopheles stephensi and An.…”
Section: Introductionmentioning
confidence: 99%
“…The chronic nature of asymptomatic malaria infection, most common in adults, in conjunction with population mobility, creates a threat to effective, long-term malaria elimination [12]. Imported asymptomatic infection often carries drug resistant strains of the Plasmodium parasite, and the transmissible stages [9,13], posing an imminent threat to receptive areas where transmission has been interrupted or targeted for elimination [14]. An improved understanding of transmission rates, Plasmodium species involved, extent of genetic diversity, and the possession of drug resistant strains of imported malaria, would permit the deployment of effective cross-border measures to limit impacts on regions targeted for elimination.…”
Section: Introductionmentioning
confidence: 99%